Effect of formation Methods on Sintering Process of Ceramic Materials: هديل سلمان سعيد (Al-Academy, 2021)
The current research is concerned with methods of formation and their effect on the sintering process of ceramic materials. The research is divided into a number of chapters. The first chapter addressed the research structure (the research problem, importance, objective, limits, and it also defined the terms used in the research). The second chapter addressed the theoretical framework, where the theoretical framework has been divided into three sections. The first section dealt with methods of formation of ceramic materials including: Plasticizing method 2- semi-dry pressing method 3- dry pressing method 4- extrusion method 5- casting method.The researcher found that there is a clear difference between the methods through her formation of tables and as it is clear in the research body. As for the second section, it addressed studying the raw ceramic materials that the researcher has classified into: 1- plastic raw materials 2- non-plastic raw materials. In the third section, the researcher addressed types and divisions of sintering: First: sintering in the solid state and its stages. Second: sintering with the presence of an effective liquid. Third: sintering by pressing and hot compression. The third chapter consists of the research procedures that addressed 1- preparing the raw material. 2- Examination of the raw material through a- chemical analysis b- metal composition c- thermal microscope examination. 3- Preparing the mixtures where four hypotheses have been put and in every hypothesis, the researcher dealt with what results from mixing the materials (Silica, crock, sodium carbonate, and kaolin under various temperatures and pressure). 4- preparing the laboratory models in which the researcher tackled 1- mixing the materials 2- forming the laboratory models 3- drying process 4-burning process 5- determining the general features for the models. The researcher has conducted some experiments to determine the features of the models after the burning process according to the following: Calculating the longitudinal contraction b- water suction c-virtual space. The fourth chapter addressed and discussed the research results. The researcher reached at the results through conducting the laboratory examinations for the samples within tables (4, 5) affixed in the research. The recommendations and suggestions put forth by the researcher to complete the scientific approach for the research are as follows: 1- not to start the research before finding the oven. 2- Conducting examinations using a thermal microscope before burning 3- burning at a slow timing rate to prevent the occurrence of distortions.